From “Screen” to “Dialogue”: The Turning Path of Children’s Philosophy Education in the Age of Digital Intelligence - Yang, Bei; Li, Renjie (Journal of Educational Research and Policies, 2025)
The deep penetration of digital technology has made children’s cognition, socialization and value construction as “digital natives” increasingly subject to technological logic. The popularization of smart terminals and algorithmic recommendations have led to the intensification of children’s screen dependence, which has led to the fragmentation of attention, emotional detachment, and superficial thinking, and has continued to impact children’s philosophical education centered on in-depth dialogues, critical thinking, and ethical reflections. Traditional philosophy education faces the challenge of adapting to the technological environment, and there is an urgent need to realize a shift from passive “screen” information consumption to active “dialogue” inquiry. This shift emphasizes the return to the essence of philosophical dialogue and the reconstruction of children’s ability to think deeply, empathy and subjectivity through equal inter-subjective interaction. The practical path should focus on the development of thinking habits and the triggering of philosophical life in terms of the target content, insist on interpersonal dialogue as the basis and technology as the supplement in terms of the methodological medium, and emphasize the guidance of dialogue and the assessment of the thinking process in terms of the evaluation of the roles, so as to make the digital intelligence tools serve rather than replace the “dialogue”, and to safeguard the children’s mobility as the main body of thinking.